Curricular training report about clinical trials monitoring on a CRO full service - Nobre, Ana Rita dos Santos (2015)
This report intends to describe the activities carried out under the traineeship which took place in the company Datamédica, Biostatistics Services and Consulting, Inc., a Contract Research Organization (CRO). The internship had the duration of 8 months during which the trainee worked as CRA being the main focus the monitoring of clinical trials. Besides the main activity, have also been developed functions adjacent to the clinical research, such as CTA and Medical Writing areas. This document tries to show the obtained vision and the points of view of the trainee while monitoring clinical trials.